2009
DOI: 10.1097/ico.0b013e31819b0385
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Endophthalmitis in Patients With the Boston Keratoprosthesis

Abstract: Endophthalmitis can occur after Boston keratoprosthesis at a significant rate, even in low-risk patients on prophylactic antibiotic drops. Given our experience with these patients and vancomycin, we recommend its prophylactic use. The increasing resistance of gram-positive organisms to fluoroquinolones and the need for close patient follow-up to encourage adherence to preventive regimens are further supported in this report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 5 publications
1
39
1
1
Order By: Relevance
“…In our series, the underlying disease was OCP in two of our patients and severe alkali burn in the remaining. Although all of the infections reported in the literature were due to gram-positive cocci [6,10], vitreous and aqueous cultures in our patients failed to isolate a responsible micro-organism.…”
Section: Discussioncontrasting
confidence: 59%
“…In our series, the underlying disease was OCP in two of our patients and severe alkali burn in the remaining. Although all of the infections reported in the literature were due to gram-positive cocci [6,10], vitreous and aqueous cultures in our patients failed to isolate a responsible micro-organism.…”
Section: Discussioncontrasting
confidence: 59%
“…But the common factor was the symptom of pain in all cases compared to only 25 % patients complaining pain in post-cataract surgery endophthalmitis in the endophthalmitis vitrectomy (EVS) study [7]. The incidence of endophthalmitis at 11.1 % in our study was between other reported incidences in literature (11.4 % and 12 [5,6]-2.5 % and 2.4 % [3,5,6,8,9]), but 158-fold higher than the incidence of endophthalmitis after cataract surgery in our institute (0.07 % culture proven endophthalmitis [10]) and 55-fold higher than penetrating keratoplasty (0.2 %). Other differences included equal distribution of bacterial and fungal infection; but this cannot be concluded emphatically due to small numbers (Table 2).…”
Section: Discussionmentioning
confidence: 42%
“…Since this device bridges the non-sterile ocular surface with sterile anterior chamber, there is increased risk of rapid invasion of pathogenic organisms through the space between the tissue and the prosthesis [2]. Additionally, infectious endophthalmitis may occur months or years after K-Pro placement [3][4][5][6]. We report the clinical characteristics, management and outcomes of five patients who developed endophthalmitis following Boston K-Pro type 1.…”
Section: Introductionmentioning
confidence: 99%
“…The greatest visionthreatening risk facing patients with any type of keratoprosthesis is bacterial endophthalmitis, most cases associated with Grampositive pathogens (2,24,27) . Early recogni tion and aggressive treatment are crucial for favorable results in the ses cases (28) . Since 1990, topical antibiotic prophylaxis has been used to prevent bacterial endophthalmitis in patients with the Bos ton KPro (25) .…”
Section: Postoperative Management and Complicationsmentioning
confidence: 99%